An RNA-seq screen of P. gingivalis LPS treated human gingival fibroblasts. (April 2018) - Xie, Yufeng; Sun, Mengjun; Xia, Yiru; Shu, Rong
Highlights: Most genes (198/204) were up-regulated at 4 h after LPS stimulation. Cytokines and chemokines showed single up-regulation peak after LPS treatment. Low dose of LPS induced single up-regulation peak of miRNA expression. High dose of LPS increased the miRNA expression at both early and late stages. Abstract: Background: In gingival tissues, lipopolysaccharide (LPS) from Porphyromonas gingivalis ( P. gingivalis ) is the most critical stimulator for inducing inflammatory response. Human gingival fibroblasts (HGFs) are the major constituents of gingival connective tissues. The aim of this study was to investigate P. gingivalis LPS induced whole transcriptional profile in HGFs and the potential crosstalk between microRNAs (miRNAs) and inflammatory cytokines. Methods: RNA-seq was performed on HGFs with and without P. gingivalis LPS treatment. The gene expression of selected inflammatory cytokines and miRNAs induced by LPS at different time points was evaluated by quantitative RT-PCR. The protein expression of chemokines was further confirmed by ELISA. Results: Interestingly, most of the significantly changed genes (198/204) were up-regulated at 4 h after 10 μg/ml LPS stimulation, including inflammatory cytokines and miRNAs. Confirmed by quantitative RT-PCR, the mRNA levels of IL-1β, IL-6 and IL-8 showed single up-regulation peak (4 h/6 h) after 1 μg/ml and 10 μg/ml LPS treatment. Similarly, 1 μg/ml LPS induced single up-regulation peak (8 h) of miRNA-146a, −146b and −155 expression. However, 10 μg/ml LPS induced the increased expression of miRNA-146a and −155 at both early stage (2 h/4 h) and late stage (24 h). Conclusion: Taken together, we investigated P. gingivalis LPS induced whole transcriptional profile, and the different behaviors of miRNA expression induced by different doses of LPS in HGFs.